BACK TO THE ORIGINS OF THE EUROPEAN UNION - TURKEY RELATIONS: ESTABLISHMENT OF AN INSTITUTIONALIZED PATHWAY AND ITS SHORTCOMINGS - Zeynep Özde Ateşok (Ankara Avrupa Çalışmaları Dergisi)
After the Athens Agreement signed with Greece, Turkey became the second associate member of the EEC with ister kin duthe signature of the 1963 Ankara Agreement which established an institutionalized pathway that is open to interpretation and contestation until today. The study offers an analysis based on archival data, secondary sources and a comparison of two association agreements which negotiated and signed at the same time-span but resulted in two different pathways. Based on new institutionalist approaches, the article aims to situate the agreement and the association in a historical and comparative context while tracing the origins and shortcomings of this institutionalized pathway which is still relevant for Turkey-EU relations.